Diffusion of chemically reacting fluids through nonlinear elastic solids: mixture model and stabilized methods. (February 2015) - Hall, R; Gajendran, H; Masud, A
This paper presents a stabilized mixed finite element method for advection-diffusion-reaction phenomena that involve an anisotropic viscous fluid diffusing and chemically reacting with an anisotropic elastic solid. The reactive fluid–solid mixture theory of Hall and Rajagopal (Diffusion of a fluid through an anisotropically chemically reacting thermoelastic body within the context of mixture theory. Math Mech Solid 2012; 17: 131–164) is employed wherein energy and entropy production relations are captured via an equation describing the Lagrange multiplier that results from imposing the constraint of maximum rate of entropy production. The primary partial differential equations are thus reduced to the balance of mass and balance of linear momentum equations for the fluid and the solid, together with an equation for the Lagrange multiplier. Present implementation considers a simplification of the full system of governing equations in the context of isothermal problems, although anisothermal studies are being investigated. The method is applied to problems involving Fickian diffusion, oxidation of PMR-15 polyimide resin, and slurry infiltration, within a one-dimensional finite element context. Results of the oxidation modeling of Tandon et al. (Modeling of oxidative development in PMR-15 resin. Polym Degrad Stab 2006; 91: 1861–1869) are recovered by employing the reaction kinetics model and properties assumed there; the only additional assumed properties are two constants describing coupled chemomechanical and purely chemical dissipation, and standard values for viscosity of air and PMR-15 stiffness properties. The present model provides the individual constituent kinematic and kinetic behaviors, thus adding rich detail to the interpretation of the process in comparison to the original treatment. The last problem considered is slurry infiltration that demonstrates the applicability of the model to account for the imposed mass deposition process and consequent effects on the kinematic and kinetic behaviors of the constituents.